Answer:
x−2x4+2x3−7x2−8x+12=x3+4x2+x−6
The rational root theorem suggests that other possible roots may be -6, 6, -3, 3, -2, 2, -1, and 1. It turns out that x=-2x=−2 is a root, since (-2)^3+4(-2)^2+(-2)-6=0(−2)3+4(−2)2+(−2)−6=0 , so x+2x+2 is also a factor and we have
\dfrac{x^4+2x^3-7x^2-8x+12}{(x-2)(x+2)}=x^2+2x-3(x−2)(x+2)x4+2x3−7x2−8x+12=x2+2x−3
Finally, we can factorize the remaining quotient easily:
x^2+2x-3=(x+3)(x-1)x2+2x−3=(x+3)(x−1)
so the other factors are x+2x+2 , x+3x+3 , and x-1x−1 .
Answer:
26/33
Step-by-step explanation:
The process is:
0.787878
78.7878
78/99x then simplify
A:line and a prism.
B:line and rectangle
Answer:
I would assume you're referring to this test? if so the answer is
a, d and e
Slope formula:
y2-y1
-------
x2-x1
48)
1-3 -2
---- = ----
-2-4 -6
So the slope of MN is 1/3